The Conquest of Bread - Kropotkin P.; Kropotkin Peter (Edmonton Black Cat Press, 2006)
The Conquest of Bread is a detailed, systematic description of how to build a future society where there is " well-being for all". It represents the most mature thought of the Russian anarchist-scientist Peter Kropotkin. Kropotkins anarchist communism is an alternative to the various forms of state socialism which have proved so disappointing in the century since this book was first published. His ideas are still refreshing and capable of providing a guide to social action.
Keywords: 32